Airports - a Platform for IoT technology? - Peter Baum (International Telecommunications Society (ITS), 2019)
This paper is a case-study exploring how and what makes IoT a very successful technology applied in the specific context of an airport. The author focuses on how IT systems and users interact in a unique environment which shares many characteristics with a city, hence the author starts his investigation into the concept of the airport as a Smart City and the Airport-City-as-a-Platform. After analyzing the City-as-a-Platform literature, notably Anttiroiko's work on the raise of participatory innovation platforms in Finnish Cities, the author posits that although cities and airports are both platforms for IT and IoT systems, cities has an inherent welfare element that airport management lacks pace key performance indicators such as Levels of Service (LOS). Moreover, the track record of IoT in the airport context, including early IoT precursors systems such as sensors and RFID tracking tags, have a longer proven record of success in the airport context, while in many other industries IoT is still an emerging technology. The airport IoT success record and challenges lend itself to closer scrutiny, notably to consider in which phase of the technology life-cycle does the success lies. Driven by the experience of his colleagues in the Connected Airport sector, the author divides the technology life-cycle phases into three segments: technology choice, technology implementation and technology optimization and operation. In order to discern the success factors that work for IoT technology in the airport context, the author devised a survey to capture the areas where colleagues agree are the most conducive to success. For the purposes of this paper, the survey on "Implementation of IoT and Digital Transformation in the Airport Industry" was created and disseminated amongst airport IoT practitioners. The paper concludes with an analysis of results.
Keywords: 330; Airports; Smart Cities City-As-A-Platform; survey; IoT integration; IoT technology maturity